Editorial Foreword: Relocating Justice in International Relations (Global Focus, 2021)
The mainstream scholarly discourse of International Relations has had tendencies to prioritize stability and order over justice because of its state-centric approach. Yet, we see how that is no longer the case in the 21st century. The question of justice becomes increasingly prevalent as transnationalism, global poverty, climate change, and human rights violation are on the rise. The notion of justice in International Relations is not only concerned about the morality or the moral worth of the individual to be treated equally, but it also deals with who deserves what, how, and why. In these uncertain times, we are facing global inequality and injustice with grievances that need to be addressed worldwide. Thus, this second edition of Journal Global Focus (JGF) Vol. 1 No. 2 is dedicated to highlighting and relocating justice.